Measurement of f1(1285) production in pp collisions at s = 13 TeV - Acharya, S.; Agarwal, A.; Aglieri Rinella, G.; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Akishina, V.; et al. (Elsevier, 2025)
This study presents the first measurement of the f 1 (1285) resonance using the ALICE detector in inelastic proton–proton collisions at a center-of-mass energy of 13 TeV. The resonance is reconstructed at midrapidity ( | y | < 0.5) through the hadronic decay channel f 1 ( 1285 ) → K S 0 K ± π ∓ . Key measurements include the determination of its mass, transverse-momentum integrated yield, and average transverse momentum. Additionally, the ratio of the transverse-momentum integrated yield of f 1 (1285) to pion is compared with calculations from the canonical statistical hadronization model. The model calculation, assuming a zero total strangeness content for f 1 (1285), reproduces the data within 1 σ deviation, shedding light on the quark composition of f 1 (1285).
Keywords: Physics; https://purl.org/pe-repo/ocde/ford#1.03.00